The relationship of knowledge, information, attitude to the handling of febine seizures toddlers in Cisungsang health center - Nurhayati Nurhayati; Nur Anita (Institute of Computer Science (IOCS), 2022)
Febrile seizures are seizures caused by a rise in body temperature of more than 38.4°C in the absence of central nervous system infection or acute electrolyte disorders in children over 1 month of age with no prior history of seizures without fever. Effective health education can only be established based on a strong understandingof knowledge, attitudes and sources of information towards action. The Research is an analytical descriptive study with a cross sectional approach, which is a study in several populations observed at the same time which aims to determine the relationship between knowledge, sources of information and maternal attitudes towards the initial treatment of febrile seizures at the Cisungsang Health Center 2022. The population and sample in this study was all mothers who had toddlers who had experienced febrile seizures in the work area of the Cisungsang Health Center from January to November 2022 which amounted to 49 mothers. The instrument used in this study was a questionnaire. Based on the results ofstatistical tests using the chi square test, the calculation results of P value = 0.000 < α 0.05 were obtained, which means that there is a relationship between knowladge, information and attitude. There is a significant relationship of knowledge, information, and attitudes with the initial management of febrile seizures in toddlers at UPTD Puskesmas Cisungsang.